2017
DOI: 10.1080/1461670x.2017.1392255
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthy Or Shady?

Abstract: Integrating user-generated content (UGC) has become an everyday practice in online journalism. Previous research suggests this can have both a beneficial and detrimental effect on a recipient's perception of online journalism's trustworthiness. We conducted an online experiment that, on the one hand, examined the overall influence of integrating UGC in an online news article compared to leaving it out altogether. On the other hand, we also analyzed how two specific modes of integrating UGC, namely its verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…Previous studies have mentioned that disheartening customer experiences are the starting point of UGC on social media and they lead to the further generation of UGC (Grosser et al, 2019;Micu et al, 2017;Kim & Lee, 2017;Gavilanes et al, 2018;Çınar, 2018;Zhao et al, 2017). Customers preferred to see content that answered their questions related to a brand in which they are interested, but their interest is socially created through everyday life and the social media interactions of SMUs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have mentioned that disheartening customer experiences are the starting point of UGC on social media and they lead to the further generation of UGC (Grosser et al, 2019;Micu et al, 2017;Kim & Lee, 2017;Gavilanes et al, 2018;Çınar, 2018;Zhao et al, 2017). Customers preferred to see content that answered their questions related to a brand in which they are interested, but their interest is socially created through everyday life and the social media interactions of SMUs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2021). Generally speaking, UGC contains a large amount of redundant information (Grosser et al. , 2019), and this information might not be relevant to the company's green value proposition.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that, compared with companies with low CSR, consumers will pay more attention to and be more involved with companies with a high CSR image and invest more cognitive effort in company-related information (Yu et al, 2021). Generally speaking, UGC contains a large amount of redundant information (Grosser et al, 2019), and this information might not be relevant to the company's green value proposition. This will increase the cognitive burden of consumers, which in turn will affect their ICGV.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Interestingly, these aspects seem to affect the evaluation of trustworthiness in opposing directions. Grosser, Hase, and Wintterlin (2017) come to a similar conclusion: Because UGC would be likely to have both positive and negative effects on the perceived trustworthiness of news stories, they tested the overall effect of integrating UGC in an online news article through an online experiment. Their data revealed that integrating UGC had a negative but overall weak effect on the perceived trustworthiness.…”
Section: Ugc In the News Coverage: The Problem Of Trustworthinessmentioning
confidence: 96%